Evaluation of the Ability of Miltefosine Associated with Topical GM-CSF in Modulating the Immune Response of Patients with Cutaneous Leishmaniasis - Fábio Peixoto; Maurício T. Nascimento; Rúbia Costa; Juliana Silva; Gaby Renard; Luiz Henrique Guimarães; Gerson Penna; Manoel Barral-Netto; Lucas P. Carvalho; Paulo R. L. Machado; Edgar M. Carvalho (Journal of Immunology Research)
Cutaneous leishmaniasis (CL) due to L. braziliensis is associated with an exaggerated inflammatory response and tissue damage. Miltefosine is more effective than pentavalent antimony (Sbv) in the treatment of CL, and here, we evaluate the ability of Sbv, miltefosine, and GM-CSF administered intravenously, orally, or topically, respectively, to modify the immune response. Patients were treated with miltefosine plus GM-CSF, miltefosine plus placebo, or Sbv. Mononuclear cells were stimulated with soluble Leishmania antigen (SLA) on day 0 and day 15 of therapy, and cytokine levels were determined in supernatants by ELISA. The lymphocyte proliferation and oxidative burst were evaluated by flow cytometry, and the degree of infection and Leishmania killing by optical microscopy. Proliferation of CD4+ T cells were enhanced in patients using miltefosine and in CD8+ T cells when GM-CSF was associated. Enhancement in the oxidative burst occurred in the miltefosine plus GM-CSF group on day 15 of therapy. Moreover, the number of L. braziliensis in infected monocytes on day 15 as well as the percentage of infected cells was lower after 48- and 72-hour culture in cells from patients treated with miltefosine plus GM-CSF. In addition to the ability of miltefosine to kill Leishmania, the changes in the immune response caused by miltefosine and GM-CSF may increase the cure rate of CL patients using these drugs.